Normalization of Card Gambling as a Social Pathology in Petuk Hamlet, Kediri Regency - Refki Rusyadi; Februana Cerly Zaelanty; Anisa Fitriyani (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This research is motivated by gambling activities that occur in the people of Petuk Hamlet. Gambling carried out by some people has undergone a normalization process through several factors. Thus, this study aims to understand how gambling activities can take place and be normalized by the people of Petuk Hamlet. This research uses a qualitative approach with a case study type of research. Through observations and interviews, the findings of the data obtained by the researcher show that gambling has become an organized local tradition or culture with a system of division of roles such as blandar, players, facility providers, and supervisors. The early history of card gambling in this study is a card game that is used as entertainment in the tradition of lek-lek-an (staying up late) during certain events. This phenomenon is in the perspective of Talcott Parsons' functional structural with the concept of AGIL (Adaptation, Goal Attainment, Integration, Latency) that the community still tries to maintain social stability despite deviant activities such as gambling. On the one hand, gambling strengthens solidarity and social relations between actors. Meanwhile, on the other hand, this activity has an impact on the economy and household life. Therefore, this study emphasizes the importance of understanding traditional gambling as part of complex rural social dynamics, where economic, cultural, and social values are intertwined.